Fatigue-less electrocaloric effect in relaxor Pb(Mg1/3Nb2/3)O3 multilayer elements. Issue 15 (December 2017) - Fulanović, Lovro; Koruza, Jurij; Novak, Nikola; Weyland, Florian; Malič, Barbara; Bobnar, Vid
Abstract: A study was made of the electrocaloric (EC) effect's stability in relaxor Pb(Mg1/3 Nb2/3 )O3 multilayer elements. The sample was subjected to 10 6 unipolar cycles at an electric field amplitude of 110 kV cm −1 . The dielectric and ferroelectric properties of the material change only slightly, while the microstructure does not reveal any detrimental evidence of the cycling. The initially measured EC temperature change of 1.45 K decreases by only 0.01 K upon cycling, exhibiting a fatigue-less behavior. The results justify the choice of relaxor multilayers as the working bodies in EC cooling devices, where the material should withstand numerous electric field cycles with high amplitudes, sometimes exceeding 100 kV cm −1 .